Az 1944-es bajmoki partizán vérengzés és annak utóélete a mai huszonévesek körében - Herczeg Zsolt (2015)
My diserretation is about the partisan reprisal in Bajmok, and it’s aftermath, which was in 1944. The bloodbath was 70 years ago, and it’s known as one the biggest tragedy for hungarian people inVojvodina. The invading partisan groups was using themethods like the system of intimidation. They was using different forms of revenge, like confiscation of property, mass executions, and constant deportations. Everybody was suspicious, who was differentin any way from the partisan ideology. The take over was at the autumn of 1944, and the purgestartedimmediately. Josip Broz Tito was the leader of this system, and the bloodshed become a taboolater. The Yugolsavian leadership was about to cover thet races of the bloodshed, the hungarian minority was unable to talk about the genocide, only rumors left for the younger generation about the truth. After that, the hungarian minority in Vojvodina was driven by fear and despair in the shadow of the newly formed system of Yugoslavia. The assimiliation of the hungarian minority was growing faster in decades later. It was a growing tendencyin mixed marriages, which is resulted in the radical identity shaping of the hungarian minority inVojvodina. This process was driven also by the bad relationship between Hungary and Yugoslavia until the late 1950’s, which caused the lack of affiliation of the hungarian minority with them other land. This caused also a very different identity development. For my studies, i’m asked young peoples in my hometown about the partisan genocide in 1944. I was curious, do they remember, and what mean to them the partisans laughter, which was 70 years ago.
Keywords: Bölcsészettudományok; Történettudomány és régészet